Annual report of the EFSA Scientific Network of Risk Assessment of Nanotechnologies in Food and Feed for 2018. Issue 4 (26th April 2019) - ; Schoonjans, Reinhilde; Eryasa, Berrak
Abstract : Regulatory preparedness is an important strategic objective of EFSA, particularly for developing techniques used in the food and feed chain such as Nanotechnologies. The Scientific Network of Risk Assessment of Nanotechnologies in Food and Feed was established in 2010 by the EFSA Advisory Forum to exchange information and expertise with Member States. Over the recent years, this Network has become more involved in regulatory preparedness through practical cooperation on a EFSA risk assessment guidance. After an extensive consultation with the Network, in July 2018, EFSA published the first part of the Guidance on the applications of nanoscience and nanotechnologies in the food and feed chain for human and animal health. The 2018 meeting was dedicated to the discussion on the implementation of this guidance and Member States presented their experiences or research linked to aspects of the EFSA Guidance. This report aims to inform the public, stakeholders and research communities about the implementation issues arising from the pilot cases and application of the EFSA Guidance. The pilot phase of the EFSA Guidance continues until the end of 2019 and further feedback is expected from Stakeholders through the workshop on 1‐2 April 2019. The Guidance will be then revised and published in 2020. The Network has also identified key topics for further research to strengthen regulatory science.